Cooperative Tandem Catalysis by an Organometallic Complex and a Metalloenzyme1. Issue 2 (25th November 2013) - Denard, Carl A.; Huang, Hua; Bartlett, Mark J.; Lu, Lu; Tan, Yichen; Zhao, Huimin; Hartwig, John F.
Abstract Although chemical and enzymatic catalysts have been combined, reactions in which an organometallic catalyst and a metalloenzyme work cooperatively to create products, which cannot be generated with either catalyst alone or in comparable yields by sequential reactions of the two catalysts, have not been reported. Such reactions are challenging to achieve, in part because the milieu in which these catalysts operate are typically different. Herein, two classes of catalysts are demonstrated to react cooperatively in the same system. Combination of a metathesis catalyst and a P450 enzyme lead to a dynamic equilibration of alkenes and a selective epoxidation of the cross‐metathesis products. These results show the potential of combining the two classes of catalysts for synthetic transformations.